2015
DOI: 10.4238/2015.october.29.25
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro inhibitory action of 17β-estradiol and environmental estrogen 4-nonylphenol on gonad-inhibiting hormone (GIH) expression in the eyestalks of Litopenaeus vannamei

Abstract: ABSTRACT. The gonad-inhibiting hormone (GIH) belongs to a neuropeptide family synthesized and released in an X-organ sinus gland complex of crustacean eyestalks. GIH inhibits crustacean ovarian maturation by suppressing vitellogenin (Vtg) synthesis, whereas estrogen is responsible for the stimulation of vitellogenesis (not established). In this study, the effects of 17β-estradiol (E 2 , 10 -6 M), estrogen receptor antagonist tamoxifen (TAM, 10 -6 , 10 -7 , and 10 -8 M), and the environmental estrogen nonylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…vannamei is predominately generated in both the brain and the eyestalk [ 15 , 16 ]. VIH -2 transcript levels have been found to increase significantly as fertilized eggs develop into juveniles, peak at sexual differentiation [ 16 ], under a negative estrogen regulation [ 30 ], and decrease in the brain after unilateral eyestalk ablation [ 15 ]. The recombinant VIH-2 protein is effective in inhibiting the hepatopancreatic Vg mRNA expression in female shrimp by both in vitro primary cell culture and in vivo injection approaches, and in reversing ovarian growth induced by eyestalk ablation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…vannamei is predominately generated in both the brain and the eyestalk [ 15 , 16 ]. VIH -2 transcript levels have been found to increase significantly as fertilized eggs develop into juveniles, peak at sexual differentiation [ 16 ], under a negative estrogen regulation [ 30 ], and decrease in the brain after unilateral eyestalk ablation [ 15 ]. The recombinant VIH-2 protein is effective in inhibiting the hepatopancreatic Vg mRNA expression in female shrimp by both in vitro primary cell culture and in vivo injection approaches, and in reversing ovarian growth induced by eyestalk ablation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated physiological responses of crustaceans to exogenously administered steroid hormones. For example, administration of 17b-estradiol advanced ovarian development (29) and stimulated vitellogenesis in female decapods (28). This compound also suppressed vitellogenesisinhibiting hormone gene-expression, which was presumably responsible for the effects on ovarian development (28).…”
Section: Responses To Exogenous Steroidsmentioning
confidence: 98%
“…For example, administration of 17b-estradiol advanced ovarian development (29) and stimulated vitellogenesis in female decapods (28). This compound also suppressed vitellogenesisinhibiting hormone gene-expression, which was presumably responsible for the effects on ovarian development (28). While 17b-estradiol administration to crayfish stimulated vitellogenin-mRNA accumulation in the hepatopancreas, progesterone administration increased vitellogenin protein levels in the hemolymph of crayfish (157).…”
Section: Responses To Exogenous Steroidsmentioning
confidence: 98%
See 1 more Smart Citation
“…This complex thus influences both gonadal development and moulting, consequently affecting organismal growth and development (Chen, Kang, Sultana, & Wilder, 2019; Liu, Kong, Chen, & Zhang, 2018; Sainz‐Hernández, Racotta, Dumas, & Hernández‐López, 2008). The eyestalk and gonads are essential for GFP growth and development, and a synergy reportedly exists between them (Jiang et al., 2018; Li et al., 2015). To the best of our knowledge, transcriptome sequencing analyses to investigate gene expression in the eyestalk and gonads have not been performed to date.…”
Section: Introductionmentioning
confidence: 99%